2019
DOI: 10.1111/acer.14199
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Mechanisms of Behaviors Associated With AUDs Using Flies and Worms

Abstract: Alcohol use disorders (AUDs) are very common worldwide and negatively affect both individuals and societies. To understand how normal behavior turns into uncontrollable use of alcohol, several approaches have been utilized in the last decades. However, we still do not completely understand how AUDs evolve or how they are maintained in the brains of affected individuals. In addition, efficient and effective treatment is still in need of development. This review focuses on alternative approaches developed over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 116 publications
(144 reference statements)
1
8
0
Order By: Relevance
“…Our results further develop the honeybee in this context [117,2628] and support previous studies showing that workers are predisposed to alcoholism [30,33]. Studies on the occurrence of alcohol dependence in other invertebrates initiated discoveries in terms of the mechanisms behind alcoholism [39]. Physiological bases of alcohol dependence in the honeybee thus deserve particular research attention, especially considering comparative aspects (e.g.…”
Section: Resultssupporting
confidence: 87%
“…Our results further develop the honeybee in this context [117,2628] and support previous studies showing that workers are predisposed to alcoholism [30,33]. Studies on the occurrence of alcohol dependence in other invertebrates initiated discoveries in terms of the mechanisms behind alcoholism [39]. Physiological bases of alcohol dependence in the honeybee thus deserve particular research attention, especially considering comparative aspects (e.g.…”
Section: Resultssupporting
confidence: 87%
“…The Drosophila model allows strict control over the genetic background, and we can rear large numbers of individuals of the same genotype under controlled environmental conditions without regulatory restrictions and at low cost. In addition, following acute exposure to alcohol, flies undergo physiological and behavioral changes that resemble human alcohol intoxication, including loss of postural control, sedation, and development of tolerance [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila melanogaster is an excellent model to study developmental effects of alcohol exposure, as we can control the genetic background and environmental conditions for large numbers of individuals without regulatory restrictions and at low cost. Importantly, flies exposed to alcohol experience loss of postural control, sedation, and development of tolerance (10)(11)(12)(13), resembling human alcohol intoxication. Previous studies on the effects of developmental alcohol exposure in Drosophila showed reduced viability and delayed development time (14,15), reduced adult body size (14) and disruption of neural development (16).…”
Section: Introductionmentioning
confidence: 99%